2004
DOI: 10.1111/j.0022-2445.2004.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Are Gay and Lesbian cohabiting couples really different from heterosexual married couples?

Abstract: Both partners from gay and lesbian cohabiting couples without children were compared longitudinally with both partners from heterosexual married couples with children (N at first assessment = 80, 53, and 80 couples, respectively) on variables from 5 domains indicative of relationship health. For 50% of the comparisons, gay and lesbian partners did not differ from heterosexual partners. Seventy‐eight percent of the comparisons on which differences were found indicated that gay or lesbian partners functioned bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
382
6
19

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(441 citation statements)
references
References 83 publications
30
382
6
19
Order By: Relevance
“…Based on the same-gender stalking studies by Pathé et al (2000) and Strand and McEwan (2011), it might be assumed that same-gender pursuers are more motivated by a resentful than by a rejected or affectionate type of motivation. A more dyadic explanation might also be plausible: It is known that same-gender couples have higher levels of equality in their relationships than opposite-gender couples (e.g., Kurdek, 2004) and that the perpetration of UPBs by more anxiously attached persons is lower when separating from a similar more anxiously attached partner than when separating from a dissimilar less anxiously attached partner (De Smet, Loeys, & Buysse, 2013). Although we did not assess both dyad members' attachment styles, it is possible that more equal attachment characteristics in samegender ex-couples buffered the perpetration of UPBs by more anxiously attached persons.…”
Section: Risk Factors Of Upbmentioning
confidence: 99%
“…Based on the same-gender stalking studies by Pathé et al (2000) and Strand and McEwan (2011), it might be assumed that same-gender pursuers are more motivated by a resentful than by a rejected or affectionate type of motivation. A more dyadic explanation might also be plausible: It is known that same-gender couples have higher levels of equality in their relationships than opposite-gender couples (e.g., Kurdek, 2004) and that the perpetration of UPBs by more anxiously attached persons is lower when separating from a similar more anxiously attached partner than when separating from a dissimilar less anxiously attached partner (De Smet, Loeys, & Buysse, 2013). Although we did not assess both dyad members' attachment styles, it is possible that more equal attachment characteristics in samegender ex-couples buffered the perpetration of UPBs by more anxiously attached persons.…”
Section: Risk Factors Of Upbmentioning
confidence: 99%
“…And indeed, contrary to many stereotypical notions about how different (or dysfunctional) same-sex relationships would be, research generally indicated that they appear to operate in largely the same manner as their heterosexual counterparts, with the same types of factors generally associated with relationship satisfaction (e.g., Kurdek, 2004; see review in Peplau & Fingerhut, 2007). Moreover, where differences have been found to exist, they may be in a positive direction, such as a greater emphasis on equality within same-sex relationships and more effective conflict resolution behaviors (e.g., Gottman et al, 2003;Kurdek, 2005).…”
Section: Through a New Lensmentioning
confidence: 81%
“…This was particularly relevant to the aforementioned debate around same-sex marriage rights. As Kurdek (2004) noted, "If marriage is to be reserved for only unions of a man and a woman, it seems reasonable to assume that opposite-sex relationships work in ways that are radically different from the way that same-sex relationships work. Comparing partners from gay and lesbian couples to spouses from heterosexual couples on variables already known to be relevant for relationship health affords one way of testing this assumption" (p. 881).…”
Section: Through a New Lensmentioning
confidence: 99%
“…Furthermore, gay, lesbian, and heterosexual individuals identified different sources of social support outside of the partnered/marital relationship; gay and lesbian couples are more likely to identify their friends as their primary source of support in general whereas heterosexual couples were more likely to identify their family members as their primary source of support (Kurdek, 2004).…”
Section: Lesbian and Gay Romantic Relationshipsmentioning
confidence: 99%